Answer:
3 divided by 10
Step-by-step explanation:
Answer:
3x - 8
Step-by-step explanation:
Step 1:
( 4x + 6 ) + ( - x + 2 )
Step 2:
4x - 6 + - x - 2
Step 3:
3x - 6 - 2
Answer:
3x - 8
Hope This Helps :)
Answer:
The standard deviation of the sample mean differences is _5.23_
Step-by-step explanation:
We have a sample of a population A and a sample of a population B.
For the sample of population A, the standard deviation
is
![\sigma_A = 17.6](https://tex.z-dn.net/?f=%5Csigma_A%20%3D%2017.6)
The sample size
is:
.
For the sample of population B, the standard deviation
is
![\sigma_B = 21.2](https://tex.z-dn.net/?f=%5Csigma_B%20%3D%2021.2)
The sample size
is:
.
Then the standard deviation for the difference of means has the following form:
![\sigma=\sqrt{\frac{\sigma_A^2}{n_A}+\frac{\sigma_B^2}{n_B}}](https://tex.z-dn.net/?f=%5Csigma%3D%5Csqrt%7B%5Cfrac%7B%5Csigma_A%5E2%7D%7Bn_A%7D%2B%5Cfrac%7B%5Csigma_B%5E2%7D%7Bn_B%7D%7D)
Finally
![\sigma=\sqrt{\frac{17.6^2}{25}+\frac{21.2^2}{30}}\\\\\sigma= 5.23](https://tex.z-dn.net/?f=%5Csigma%3D%5Csqrt%7B%5Cfrac%7B17.6%5E2%7D%7B25%7D%2B%5Cfrac%7B21.2%5E2%7D%7B30%7D%7D%5C%5C%5C%5C%5Csigma%3D%205.23)
Answer:96.97
Step-by-step explanation:
Given
mean height of women ![\mu _w=64](https://tex.z-dn.net/?f=%5Cmu%20_w%3D64)
Standard deviation of height ![\sigma _w=2.82](https://tex.z-dn.net/?f=%5Csigma%20_w%3D2.82)
mean height of men ![\mu _=69.3](https://tex.z-dn.net/?f=%5Cmu%20_%3D69.3)
Standard deviation of height ![\sigma _m=2.71](https://tex.z-dn.net/?f=%5Csigma%20_m%3D2.71)
P![\left ( X](https://tex.z-dn.net/?f=%5Cleft%20%28%20X%3C69.3%5Cright%20%29)
P![\left ( \frac{x-\mu _w}{\sigma _w}\right )](https://tex.z-dn.net/?f=%5Cleft%20%28%20%5Cfrac%7Bx-%5Cmu%20_w%7D%7B%5Csigma%20_w%7D%5Cright%20%29%3CP%5Cleft%20%28%20%5Cfrac%7B69.3-64%7D%7B2.82%7D%5Cright%20%29)
P![\left ( Z](https://tex.z-dn.net/?f=%5Cleft%20%28%20Z%3C1.8794%5Cright%20%29)
i.e. 0.9697=96.97 %
The first step for solving this expression is to insert what a and b stand for into the expression. This will change the expression to the following:
2(2)(4)³ + 6(2)³ - 4(2)(4)²
Now we can start solving this by factoring the expression
2(2 × 4³ + 3 × 2³ - 4 × 4²)
Write 4³ in exponential form with a base of 2.
2(2 ×
![2^{6}](https://tex.z-dn.net/?f=%202%5E%7B6%7D%20)
+ 3 × 2³ - 4 × 4²)
Calculate the product of -4 × 4².
2(2 ×
![2^{6}](https://tex.z-dn.net/?f=%202%5E%7B6%7D%20)
+ 3 × 2³ -4³)
Now write 4³ in exponential form with a base of 2.
2(2 ×
![2^{6}](https://tex.z-dn.net/?f=%202%5E%7B6%7D%20)
+ 3 × 2³ -
![2^{6}](https://tex.z-dn.net/?f=%202%5E%7B6%7D%20)
)
Collect the like terms with a base of 2.
2(
![2^{6}](https://tex.z-dn.net/?f=%202%5E%7B6%7D%20)
+ 3 × 2³)
Evaluate the power of 2³.
2(
![2^{6}](https://tex.z-dn.net/?f=%202%5E%7B6%7D%20)
+ 3 × 8)
Evaluate the power of
![2^{6}](https://tex.z-dn.net/?f=%202%5E%7B6%7D%20)
.
2(64 + 3 × 8)
Multiply the numbers.
2(64 + 24)
Add the numbers in the parenthesis.
2 × 88
Multiply the numbers together to find your final answer.
176
This means that the correct answer to your question is option A.
Let me know if you have any further questions.
:)